2022
DOI: 10.3390/molecules27030651
|View full text |Cite
|
Sign up to set email alerts
|

Production of an Anise- and Woodruff-like Aroma by Monokaryotic Strains of Pleurotus sapidus Grown on Citrus Side Streams

Abstract: The production of natural flavors by means of microorganisms is of great interest for the food and flavor industry, and by-products of the agro-industry are particularly suitable as substrates. In the present study, Citrus side streams were fermented using monokaryotic strains of the fungus Pleurotus sapidus. Some of the cultures exhibited a pleasant smell, reminiscent of woodruff and anise, as well as herbaceous notes. To evaluate the composition of the overall aroma, liquid/liquid extracts of submerged cultu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 70 publications
0
9
0
1
Order By: Relevance
“…20 In a recent study, P. sapidus produced up to 160 mg p-anisaldehyde per liter of culture medium, and further supplementation studies using labeled tyrosine revealed the formation of labeled panisaldehyde. 21 Thus, an analogous biosynthetic pathway compared to B. adusta and the presence of an OMT in the biosynthesis of p-anisaldehyde in P. sapidus seemed evident. However, enzymes involved in potential methylation reactions catalyzing the formation of p-anisaldehyde are so far unknown.…”
Section: ■ Introductionmentioning
confidence: 92%
“…20 In a recent study, P. sapidus produced up to 160 mg p-anisaldehyde per liter of culture medium, and further supplementation studies using labeled tyrosine revealed the formation of labeled panisaldehyde. 21 Thus, an analogous biosynthetic pathway compared to B. adusta and the presence of an OMT in the biosynthesis of p-anisaldehyde in P. sapidus seemed evident. However, enzymes involved in potential methylation reactions catalyzing the formation of p-anisaldehyde are so far unknown.…”
Section: ■ Introductionmentioning
confidence: 92%
“…While the potential of basidiomycetes for the production of volatile flavours is clearly far from being fully exploited, solid-state [115] and submerged cultures [116] were shown to provide suitable experimental systems to valorise renewable biomass from food processing, such as pomace, molasses, leaves or peels. This allows the use of non-food biomass as a cheap source of nutrients and, at the same time, provides a sink for these large volume side-streams.…”
Section: Formation Of Volatile Flavoursmentioning
confidence: 99%
“…Bürger et al [ 3 ] investigated the production of an anise- and woodruff-like aroma using monokaryotic strains of Pleurotus sapidus grown on citrus side streams. Their main conclusions highlighted the role of the character impact compound p -anisaldehyde in the anise- and woodruff-like note while the acyloin identified as (2S)-hydroxy-1-(4-methoxyphenyl)-1-propanone also contributed to the overall aroma.…”
Section: Highlights Of the 16th Editionmentioning
confidence: 99%